An MRI Evaluation of Patients Who Underwent Treatment with a Cell-Mediated Gene Therapy for Degenerative Knee Arthritis: A Phase IIa Clinical Trial - Cho, Jung Jong; Totterman, Saara; Elmallah, Randa K.; Kim, Tae Won; Lee, Bumsup; Mont, Michael A. (The Journal of Knee Surgery, 2017)
Multiple therapies have been developed to slow down the progression of knee osteoarthritis (OA), with the aim of avoiding or delaying TKA. One such potential method is cell-mediated gene therapy, which utilizes allogeneic human chondrocytes modified to express transforming growth factor-β1. Using magnetic resonance imaging (MRI), we evaluated patients who underwent treatment with this injection in a Phase II study and assessed structural changes in: (1) bone marrow edema lesions, (2) cartilage defect depth and surface area, (3) articular bone surface and osteophytes, and (4) meniscus structure and signal, as well as changes in (5) joint fluid, (6) periarticular inflammation, and (7) synovial inflammation. Twenty-seven patients (6 men and 21 women) who had late-stage OA were randomized 1:1 to receive a 3:1 mixture of nontransduced chondrocytes and genetically engineered chondrocytes, at doses of 6 × 106 cells (group 1) or 1.8 × 107 cells (group 2). MRI was performed at baseline (preinjection), and at 6 and 12 months postinjection. The whole-organ MRI score system was used to assess the aforementioned changes. Treatment was considered to be successful if patients experienced an improvement in or no change in their scores, indicating that the disease had not progressed. All patients in both cohorts individually demonstrated an improvement or no change in one or more of the assessment parameters. At 6 months, the low-dose cohort demonstrated worsening in mean scores in one parameter (bone surface and osteophytes), while the high-dose cohort demonstrated no worsening in mean scores. At 12 months, the low-dose cohort had worsening in the mean score in a subset of one parameter (cartilage signal intensity), and the high-dose cohort demonstrated worsening in mean scores in two parameters (bone surface osteophytes and periarticular inflammation). This is the first study to evaluate MRI changes in patients treated with this injection. These findings provide an impetus for further research on this topic, as well as a starting point for Phase III testing.
Keywords: MRI; cartilage regeneration; osteoarthritis; TissueGene-C